Determinants of intellectual capital performance in Iraq banks - Bahaaldin, Noora Sabah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
Currently, intellectual capital has emerged to become the backbone of any successful business activity. Thus, the performance of intellectual capital in Iraqi banks is a subject of this study that aims to examine the factors that determinants intellectual capital performance which are (bank profitability, efficiency of investment in IC, bank risk, and barriers to entry). The research was based on secondary data for the annual financial reports of Iraqi banks for the years 2006-2011 where the study utilised sixteen banks listed in the Securities Commission of Iraq. Pulic Model is used as a measurefor VAIC and the data collected was analyzed using several methods such as Pearson Correlation and General Linear Regression. A total of four research questions are developed to examine the associations between intellectual capital performance (dependent variable), and profitability of banks, efficiency of investment in IC, bank risk and barriers to entry (independent variables).Findings showed a statistically significant relationship between the independent variables and the dependent variable, and thus, it supported three out of four research hypotheses. The study suggests additional research to examine the determinants of ICP prior to any generalization of the study results. Moreover, the empirical tests are confined to Iraqi bank sector for the period 2006-2011 and thus, the study results may not be extended to other sectors or to other study periods. The study highlights the importance of being identify the factors that determine intellectual capital performance which in turn increase the ability of banking performance. Moreover, results of this research are in addition to other sources related to the performance of intellectual capital in Iraq, as it provided additional vision for the rest of the researchers for the purpose of development of research in this area.